Chemical characteristics of pyrites in the Derince sulfide deposit (Elazig, Eastern Turkey) - Temur, S.; Boeluecek, C.; Akguel, M.; Orhan, H. (Maik Nauka/Interperiodica/Springer, 2008)
[Abstract Not Available]
Keywords: Hosted Massive Sulfide; Proton-Microprobe Analyses; Trace-Elements; Gold; Mineralization; Chalcopyrite; Australia; Chemistry; Minerals; Manitoba